ANALISIS DAMPAK PENGGUNAAN KECERDASAN BUATAN (AI) GENERATIF DALAM PENDIDIKAN TERHADAP MOTIVASTI BELAJAR DAN INTEGRITAS AKADEMIK - Gemini Tambunan; Nita Delila Tamba; Andi Nova; Sulvia Reresunita Panjahitan (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
This study aims to analyze the impact of generative artificial intelligence (AI) use in education on students’ learning motivation and academic integrity. The rapid development of generative AI technologies, such as ChatGPT, Gemini, and similar platforms, has significantly influenced learning processes, affecting both cognitive engagement and academic behavior. This research examines how generative AI can enhance learning motivation by providing instant information access, personalized learning materials, and more flexible learning assistance. However, its use also raises critical concerns regarding academic integrity, including increased risks of plagiarism, academic dishonesty, and reduced learner autonomy. The findings indicate that generative AI has a dual effect: offering opportunities to improve learning quality while simultaneously demanding strong regulation, ethical guidelines, and digital literacy to prevent erosion of academic values. Therefore, educational institutions must implement comprehensive policies, guidance, and supervision to ensure that generative AI is utilized ethically and constructively.